The multifaceted dimensions of potent nanostructures: a comprehensive review. (5th March 2021) - Jamwal, Deepika; Sharma, Aashima; Kanwar, Rohini; Mehta, Surinder Kumar
Abstract : Nanoscience as a powerful general-purpose technology for commercialization. Abstract : Nanotechnology has been accepted as a successful general-purpose technology and engine for growth in the 21st century. Research in the last two decades has highlighted the numerous potential applications of nanomanufacturing and commercialization. Nanotechnology has revolutionized various aspects of different areas, like cosmetics, medicines, medical devices, pharmaceuticals, cement, agriculture, electronics, etc. Effective commercialization is of prodigious importance to inventive firms, and the latest literature has progressively recognized that industry has involvement not only in research and development but also in commercialization. Research into nanotechnology is extremely broad and involves different products, such as in the fields of cosmetics, medicines, medical devices, electronics, cement, etc. ; many examples have already been commercialized and others are in development. The present review article explores recent developments relating to industrial nanotechnology and nanotechnology commercialization, which involves the development of products and techniques with a view toward their commercialization.